2019
DOI: 10.1136/bmjopen-2018-026470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an integrated care pathway on use of primary and secondary healthcare by patients at high risk of emergency inpatient admission: a matched control cohort study in Tower Hamlets

Abstract: ObjectivesTo assess the effects of an integrated care pathway on the use of primary and secondary healthcare by patients at high risk of emergency inpatient admission.DesignObservational study of a real-life deployment of integrated care, using patient-level administrative data. Regression analysis was used to compare integrated care patients with matched controls.SettingA deprived, inner city London borough (Tower Hamlets).Participants1720 patients aged 50+ years registered with a general practitioner in Towe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Within our own work and elsewhere, we have found a number of curious cases in which the data suggest that people receiving integrated care were using some hospital services more than a carefully selected group of matched controls. [1][2][3] Studies like these stick out, even in an equivocal evidence base that cannot agree whether integrated care initiatives can reduce the use or cost of services in the community and in hospitals. [4][5][6][7] The curious studies we highlight raise questions about why such unexpected results are still being found decades into the integrated care journey in England, and whether the aims of integration, specifically surrounding reducing hospital admissions and improving system efficiency, will ever be consistently achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Within our own work and elsewhere, we have found a number of curious cases in which the data suggest that people receiving integrated care were using some hospital services more than a carefully selected group of matched controls. [1][2][3] Studies like these stick out, even in an equivocal evidence base that cannot agree whether integrated care initiatives can reduce the use or cost of services in the community and in hospitals. [4][5][6][7] The curious studies we highlight raise questions about why such unexpected results are still being found decades into the integrated care journey in England, and whether the aims of integration, specifically surrounding reducing hospital admissions and improving system efficiency, will ever be consistently achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of which interventions work to reduce PPH is evolving over time and many interventions, whilst demonstrating improvements in quality of life measures and patient satisfaction do not report improvements in hospital admissions [ 6 , 33 , 34 , 40 , 41 ]. Indeed some studies have reported interventions which have led to increased admissions [ 6 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the hierarchical structure of the health system, IPSCS can bring "closer-to-community services" within broader management (organizational integration) or provide the opportunity for functional, clinical, or service level integration (4). It opens the prospect for organized service delivery between primary care provider and specialist, leading to early detection of disease, improved quality of care, better follow-up, and patient outcome (6-10)-howevereffectiveness of the integration varies by context and interventions (11).…”
Section: Figure 1: Complexity Of Vertical Integration Within Health Smentioning
confidence: 99%